Reflection on two poems: Aleixandre` s "Mar del Paraíso" and Masefield` s "Sea Fever" - Quirós García, Elizabeth (2018)
In this article we analyze the presence of the sea in both poems "Mar del Paraíso" (Sea of Paradise) by the Chilena poet Vicente Aleixandre, and "Sea Fever" by the English poet John Masefield.